Pengaruh Penerapan Customer Relationship Management Terhadap Kepuasan Pasien di Rumah Sakit Onkologi Surabaya - Mega Restria Nindya Mesti (JURNAL PENELITIAN KESEHATAN, 2016)
Number of patient revisit in outpatient unit in Hospital of Oncology Surabaya  decreased in the period 2012 – 2014 amounted to 13,5%. Though Hospital of Oncology Surabaya  has implemented customer relationship management strategy in order to increase patient satisfaction and imrove patient loyalty. The purpose of this study was to analyze the effect of implementation of customer relationship management to patient satisfaction in Hospital of Oncology Surabaya.This research was an observational analytic research. The result showed that the implementation of customer relationship management affect significantly to patient satisfaction (sig. = 0,000). The improvement in customer relationship management implementation would affected in patient satisfaction amounted to 14,7%. Keywords: customer relationship management, patient satisfaction, Hospital of Oncology Surabaya.